(Re) Constructing scenarios for action in mental health in the Family Health Strategy - José Ferreira Lima Júnior; Thaliny Batista Sarmento de Oliveira; Francisca Bezerra de Oliveira; Helena Karolyne Arruda Guedes (Universidade de Fortaleza, 2011)
Objectives: To assess the interaction between mental health and primary care, as well as analyze if these services enable the embracement process and reintegration of users in family and community. Methods: An exploratory study with qualitative approach developed in 13 basic health units (UBS) and type II Center of Psychosocial Attention (CAPS II) in Cajazeiras-PB, Brazil. The instruments used in data collection were simple observation,field diaries and semi-structured interview. Study subjects were nurses of UBS and graduate professionals of CAPS II. Results: We perceive the lack of coordination between the Family Health Strategy team and Mental Health team, resulting in the care provided to the user with mental distress centered in CAPS II with no coordination with primary care network. Conclusion: The lack of integration between ESF and CAPS II regarding the care provided to the user with psychological distress indicate the need for deployment of municipal public policies that promote the interrelationship between mental health and primary care network.